President’s Power, Transition, and Good Governance - Mochtar, Zainal Arifin; Afkar, Kardiansyah (Sebelas Maret University Faculty of Law, 2022)
This study aims to analyze the President's power and the threat attached to it during the transition of the inter-election period and the concept of the legal framework in Indonesia's legal system. It also provides the need to be performed in the future to ensure that the President does not abuse this power. The matter raises a series of problems regarding the government's authority during the election transition period. This research will provide comparative studies with Ghana, Liberia, and the United States to understand the President's power in the Indonesian constitutional system. This research was conducted using doctrinal research methods, or normative legal research. In reviewing a legal issue, a doctrinal research method analyzes positive law, related cases, and other relevant references. The results showed that the President's power during the election transition period needs to be regulated in the constitution. Furthermore, the arrangement has to be enforced technically in the form of a presidential transition law.